Collection development of non print materials in Filipino Chinese schools in Metro Manila - Singian, Ma. Alma Navarro (School of Library and Information Studies, University of the Philippines Diliman, 2010)
Collection development of non-print materials is important today because of the rapid changes in technology. In developing library collection, the school must have a written collection development policy. Developing and managing materials for the Instructional Materials Center have assumed more importance in recent years. For school libraries, collections must serve the academic programs of its community. Likewise, collection is built to support the instructional programs of the schools, thus, only that which can strengthen its program must be made available.